The Effects of Different Aquaponic System Designs (NFT and DWC) on Water Quality, Growth, and Survival of Nile Tilapia (Oreochromis niloticus) - Lubis, Kaisa Alhani; Siswoyo, Bambang Hendra; Afriani, Dwi Tika (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the effects of different aquaponic system designs, namely Nutrient Film Technique (NFT) and Deep Water Culture (DWC), on water quality, growth, survival rate, and feed efficiency of Nile tilapia (Oreochromis niloticus). The experiment was conducted for 30 days in the Wet Laboratory of the Aquaculture Study Program, Faculty of Fisheries, Dharmawangsa University, using a Completely Randomized Design (CRD) with three treatments and three replicates: control (without hydroponics), DWC, and NFT. The observed parameters included absolute weight gain, absolute length gain, specific growth rate (SGR), survival rate (SR), feed conversion ratio (FCR), and water quality (temperature and pH). Data were analyzed using ANOVA at a 95% confidence level (α = 0.05). The results showed that differences in aquaponic system design had a significant effect (P < 0.05) on the growth and survival of Nile tilapia. The DWC treatment produced the highest absolute weight gain of 8.5 g with a survival rate of 100%, whereas the NFT system resulted in a weight gain of 5.8 g with a survival rate of 80%. The lowest FCR was recorded in the DWC system (1.00), compared with NFT (1.07) and the control (1.25). Water quality remained within the optimal range throughout the study, with temperatures of 26–31°C and pH values of 6.6–7.2. It can be concluded that the DWC system was more effective than the NFT system and the control in improving the growth and survival of Nile tilapia.